What are design and technology teachers doing in response to a subject change? - Davies, Sarah (2022)
In 2014, the secondary subject, design and technology, went through a fundamental policy reform that impacted teachers and their work. Previous research into teachers and subject change in secondary design and technology highlighted the challenge of subject change to established ways of working and the problems associated with teachers’ perceptions of practice. However, these studies focused on a different iteration of the subject and teacher experience, exposing a gap in empirical research about the current iteration of the subject and teacher experience. Therefore, this research aimed to investigate the factors influencing design and technology teachers’ capacity to translate policy into practice.